2007
DOI: 10.1136/jcp.2005.035808
|View full text |Cite
|
Sign up to set email alerts
|

Oral phaeohyphomycosis: Figure 1

Abstract: This is the first description of solitary phaeohyphomycosis affecting the mucosal surface. The lesion developed in the inferior lip of a 57-year-old woman. After surgical resection, histopathological examination evidenced characteristic brownish fungal structures within granulomatous–purulent inflammation. Amplification and sequencing of rDNA obtained from paraffin-embedded tissue identifiedAlternariaspecies, as the causative agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
3
9
0
2
Order By: Relevance
“…An unspeciated organism of the genus Alternaria was reported to cause a single, oral, nodular lesion in an affected human. 26 In the present case, the oral lesions were, perhaps, macroscopically more comparable with the lesions described in candidiasis of humans 27 and, more rarely, dogs. 28 However, material from the lip and tongue lesions failed to yield fungal elements on culture and, as biopsy would have required general anaesthesia, this was not carried out on this compromised patient.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…An unspeciated organism of the genus Alternaria was reported to cause a single, oral, nodular lesion in an affected human. 26 In the present case, the oral lesions were, perhaps, macroscopically more comparable with the lesions described in candidiasis of humans 27 and, more rarely, dogs. 28 However, material from the lip and tongue lesions failed to yield fungal elements on culture and, as biopsy would have required general anaesthesia, this was not carried out on this compromised patient.…”
Section: Discussionsupporting
confidence: 84%
“…An unspeciated organism of the genus Alternaria was reported to cause a single, oral, nodular lesion in an affected human 26 . In the present case, the oral lesions were, perhaps, macroscopically more comparable with the lesions described in candidiasis of humans 27 and, more rarely, dogs 28 .…”
Section: Discussionsupporting
confidence: 71%
“…It could be interpreted as an additional evidence for a traumatic route of infection, as this population has been anecdotally quoted to chew vegetable residues and to use plant fragments as toothpicks. We have recently observed a case of another rare oral mycosis that could be explained by local inoculation 30 . Others have made similar observations, 31–33 and experimental works have suggested that laminin in the basal lamina of the oral mucosa could favour installation of P. brasiliensis , possibly through adhesion‐mediated gp43 34 .…”
Section: Discussionmentioning
confidence: 62%
“…We have recently observed a case of another rare oral mycosis that could be explained by local inoculation. 30 Others have made similar observations, [31][32][33] and experimental works have suggested that laminin in the basal lamina of the oral mucosa could favour installation of P. brasiliensis, possibly through adhesion-mediated gp43. 34 Oral mucosal infection by direct inoculation has been critically questioned in a recent experimental study.…”
Section: Discussionmentioning
confidence: 68%
“…While subcutaneous infections by dematiaceous fungi secondary to traumatic implantation have been described in human subjects, intraoral infection by these microorganisms has been previously reported in at least two cases, one involving the lower labial mucosa [5] and the other infecting a third molar extraction socket [6]. We present a case of oral phaeohyphomycosis within an epitheliumlined cyst of the anterior midline hard palate.…”
Section: Introductionmentioning
confidence: 86%